2010
DOI: 10.1073/pnas.1012406108
|View full text |Cite
|
Sign up to set email alerts
|

Timing and completion of puberty in female mice depend on estrogen receptor α-signaling in kisspeptin neurons

Abstract: Puberty onset is initiated by activation of neurons that secrete gonadotropin-releasing hormone (GnRH). The timing and progression of puberty may depend upon temporal coordination of two opposing central mechanisms-a restraint of GnRH secretion before puberty onset, followed by enhanced stimulation of GnRH release to complete reproductive maturation during puberty. Neuronal estrogen receptor α (ERα) has been implicated in both controls; however, the underlying neural circuits are not well understood. Here we t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
253
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(285 citation statements)
references
References 47 publications
(48 reference statements)
27
253
1
4
Order By: Relevance
“…Adolescence is characterized by significant brain maturation and pubertal differentiation,23, 24, 25, 26, 27, 37, 38, 39, 40, 41 suggesting that the pathophysiological response to mTBI and RmTBI might differ from adults, the most commonly studied population. There is also a gap in the literature with respect to how the female brain responds to mTBI.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence is characterized by significant brain maturation and pubertal differentiation,23, 24, 25, 26, 27, 37, 38, 39, 40, 41 suggesting that the pathophysiological response to mTBI and RmTBI might differ from adults, the most commonly studied population. There is also a gap in the literature with respect to how the female brain responds to mTBI.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive experimental studies in various species have demonstrated that kisspeptin-producing neurons are major afferents to GnRH neurons and are essential for different aspects of GnRH function, ranging from the tonic feedback control of GnRH and/or gonadotropin secretion to generation of the pre-ovulatory surge responsible for ovulation. 43 Interestingly, although kisspeptins do not seem to be mandatory for proper GnRH neuron migration, compelling experimental work has documented that populations of kisspeptin neurons undergo a dynamic process of prenatal and postnatal maturation that enables them to establish connections with GnRH neurons early in development 44 (under the control of steroid hormones [45][46][47] ). Similarly, identification of mutations in TAC3 (encoding tachykinin-3, which is cleaved to form neurokinin-B) and TACR3 (encoding tachykinin receptor 3; also known as neuromedin-K receptor [NKR]) [48][49][50] in patients with CHH highlights the important role of members of the tachykinin family in the control of GnRH neurons.…”
Section: Biology Of the Gnrh Neuronal Systemmentioning
confidence: 99%
“…Des analyses des variants polymorphes humains des gènes ERα et ERβ suggèrent que la présence de certains variants est corrélée avec une élévation de l'âge de la puberté, et que des polymorphismes combinés de ces deux gènes pourraient influencer encore plus l'âge de l'apparition des premières règles chez les filles [5,6]. Chez la souris, l'invalidation sélective de l'ERα dans les neurones à kisspeptine entraîne un arrêt de la maturation pubertaire conduisant à une infertilité [7]. Ces données indiquent un rôle important de la voie de signalisation de l'ERα dans la régu-lation de la mise en place de la puberté par l'oestradiol.…”
Section: Le Récepteur Neural Des Oestrogènes Bêtaunclassified
“…De manière intéressante, la délétion de l'ERα dans les cellules à kisspeptine résulte en une avancée de l'âge de la puberté chez la souris [7]. Nous avons donc cherché à déterminer si la délétion de l'ERβ central affectait l'expression de l'ERα, entraînant ainsi le retard pubertaire observé.…”
Section: Déclenchement De La Puberté : Relation De Yin Yang Entre Eraunclassified